Efficiency of Marine Dry Fish Marketing in Bangladesh: A Supply Chain Analysis (The Agriculturists, 2016)
The marine dried fishes have the demand both in domestic and international market. Bangladesh has a great potentiality to earn huge foreign exchange by exporting marine dry fishes. The present study was designed to analyze the supply chain and to examine marketing efficiency of marine dry fish in Bangladesh. Data were collected from 170 stakeholders and 9 export oriented firms/agencies using face to face semi-structured interviews considering 9 major species of marine fishes. A number of FGDs were conducted to supplement the information collected through survey method. The study areas were purposively selected. Three types of market such as primary market, secondary market and consumer market were considered for data gathering. High priced fish demanded high marketing cost resulting higher marketing margin and profit compared to low priced fish. Processing and transportation costs were also higher for high valued species compared to the low valued ones. Marketing margin and marketing profit were very high in export market compared to domestic market. However, shorter supply chains (channels) were more efficient than longer supply chains.The Agriculturists 2015; 13(1) 53-66